ATTACK ON WATER BY CARBON OF SOLID FUEL - N. S. Nazarov; A. I. Olevanov (Наука и техника)
The paper considers a continuous method for attack of high temperature water steam by carbon of solid fuel (coke). Design of water-coal gas generator and experimental stand, methodology for  measurements of parameters of water-coal gasification are described in the paper.